Theory of mind and impulsivity mediate the relationship between anxiety and non-suicidal self-injury in adolescents with depressive disorder - Huang, Fangjun; Zeng, Jing; Huang, Shiwei; Liu, Tiebang; Wang, Guojun (Scientific reports, 2025)
Impairment in Theory of Mind (ToM) may serve as a mediator in the relationship between anxiety, depression emotions and non-suicidal self-injury (NSSI) in adolescent patients with depressive disorders. This study aimed to examine the mediating roles of ToM and impulsivity in the link between anxiety, depression, and NSSI in first-time hospitalized adolescents with depressive disorders. A total of 52 adolescents patients were recruited from Shenzhen Kangning Hospital. Anxiety, depression, impulsivity, NSSI, cognitive ToM, and affective ToM were assessed using the Hamilton Anxiety Rating Scale, Hamilton Depression Rating Scale, Barratt Impulsivity Scale, Adolescent Self-Harm Scale, Yoni task, and Hinting task. A structural equation model was developed using AMOS 24.0 to investigate the underlying mechanisms of NSSI. Our results indicate that anxiety not only directly contributes to NSSI but also exerts its influence through two indirect pathways: impairing cognitive ToM and disrupting affective ToM, which heightens impulsivity. These mechanisms may further increase the likelihood of NSSI (CMIN = 5.168, CMIN/DF = 1.292, P = 0.270, GFI = 0.964, AGFI = 0.864, TLI = 0.929, RMSEA = 0.076). These results highlight the importance of interventions aimed at reducing anxiety and impulsivity while enhancing ToM abilities to help mitigate NSSI risk in adolescents with depressive disorders.